Konsep Diri, Kecerdasan Emosi dan Perilaku Asertif pada Siswa SMA Kelas X - Riska Muliati (Psyche 165 Journal, 2021)
This assertive behavior becomes an important thing to pay attention to generally for each individual and especially for individuals who are studying, namely students to be more able to optimize their potential. This study want to inform the impact of : (1) self-concept and assertive behavior in high school students in class X, (2) emotional intelligence and assertive behavior in high school students in class X, (3) self-concept and emotional intelligence in students' assertive behavior in high school class X. This study uses a correlational quantitative method. Researchers used as many as 100 high school students in class X as the study sample selected using random sampling techniques. The data analysis technique used in this research is multiple linear regression analysis test. The results of this study indicate that: (1) self-concept has a significant effect on assertive behavior with a positive relationship direction that can be seen from the significance value of 0.005 and the regression coefficient of 0.315. (2) emotional intelligence has a significant effect on assertive behavior with a positive relationship direction that can be seen from the significance value of 0,000 and a regression coefficient of 0.414. RSquare value of 0.464; that is, 46.4% of the variation in assertive behavior is influenced by self-concept variables and emotional intelligence and the remaining 53.6% is caused by other variables not measured by researchers. The relationship between self-concept and emotional intelligence with assertive behavior is known to have a significant relationship with a significance value of 0,000.